Aktualisasi Jemaat Rumah Tangga Sebagai Strategi Perintisan Gereja - Purdaryanto, Samuel (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
Church planting is part and implementation of the Great Commission. The command to go make disciples has the goal of planting a congregation. Church planting faces challenges in its implementation, both internal and external factors. The church's lack of seriousness in preaching the gospel and the comfort of the local church are internal, cultural, societal factors and intimidation is also an external factor inhibiting church planting, so a strategy is needed. The aim of the research is to explain how home congregations are a strategy in church planting. This research uses a qualitative approach with a literature study method to examine home congregations that can be used in planting churches. The results of this research found that there is a biblical basis for the practice of home congregations, home congregations that are cheap and effective and home congregations that are easy to multiply. The novelty of this research lies in the use of home congregations as a church planting strategy with an emphasis on discipleship through home congregations in planting churches.